Stroboscopic image synthesis of sports player from hand-held camera sequence - Hasegawa, K.; Saito, H. (IEEE International Conference on Computer Vision (ICCV) Workshops, 2015, Santiago, 2015)
A method for synthesizing the stroboscopic image of a moving sports player from a hand-held camera sequence is proposed. In this method, a player is extracted from each frame of an input video sequence using a HOG-based people detector. After removing the bounding box of the extracted player from each frame, all frames are stitched together to generate a background image without the player. The player's area is then overlaid onto the stitched background image and a stroboscopic image of the player is synthesized. By using the bounding box of the player detected by HOG and by subtracting the images, computational speed and accuracy can be improved compared with the conventional method that segments the player's region. In addition to the stroboscopic image synthesis, we also remove the player's shadow to improve the appearance of the resultant stroboscopic image. Experimental results demonstrate the effectiveness of the proposed method.